2023
DOI: 10.1111/hae.14761
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID‐19 related hospitalizations and mortality in adults aged ≥40 years with haemophilia: A survey from Europe

Abstract: At the beginning of the COVID-19 (SARS-CoV-2) pandemic, it was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Hermans et al conducted a study on over 20 hemophilia treatment centers and found four deaths (0.1%) among 4,050 patients with hemophilia during the COVID-19 pandemic. 19 Similarly, we did not find any deaths among our cohort of approximately 12,000 patients with CBDs in Iran. 29 In comparison, the World Health Organization reported a mortality rate of 7% across all age groups in the general population during the initial phase of the pandemic before widespread vaccination was available.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Hermans et al conducted a study on over 20 hemophilia treatment centers and found four deaths (0.1%) among 4,050 patients with hemophilia during the COVID-19 pandemic. 19 Similarly, we did not find any deaths among our cohort of approximately 12,000 patients with CBDs in Iran. 29 In comparison, the World Health Organization reported a mortality rate of 7% across all age groups in the general population during the initial phase of the pandemic before widespread vaccination was available.…”
Section: Discussionsupporting
confidence: 45%
“…The exact number of CBD patients with COVID-19 was not reported in four studies ( n = 251, 32.5%). 8 15 19 21…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations